(untitled) (Stamford Journal of English, 2013)
Selecting a right way to provide students with error feedback in their writing has proved to be a complex task for researchers in language pedagogy. Although a lot of studies have been conducted to examine this issue, the teachers are still following their own way of error feed back. So the researchers feel that there is a need to conduct different sort of studies to find out an effective way of error feedback. The present study with 20 participants in second trimester university level proves that students prefer coded feedback more as in this process of error feedback teachers show the error and its type by using a certain code or symbol. This study also shows that the students benefit more from having coded feedback over non-coded feedback. DOI: http://dx.doi.org/10.3329/sje.v7i0.14463 Stamford Journal of English; Volume 7; Page 62-86